Editor's Choice – Effect of Branch Stent Choice on Branch-related Outcomes in Complex Aortic Repair. Issue 4 (April 2016) - Mastracci, T.M.; Carrell, T.; Constantinou, J.; Dias, N.; Martin-Gonzalez, T.; Katsargyris, A.; Modarai, B.; Resch, T.; Verhoeven, E.L.G.; Burnell, M.; Haulon, S.
Abstract : Objectives: The use of branched stent grafts for the treatment of thoracoabdominal aneurysms [TAAA] is increasing, but mating stent graft choice has not been studied. This study combined experience of five high volume centres to assess a preferred mating stent. Methods: Data from five centres were retrospectively combined. Patients were included if they underwent stent graft for treatment of TAAA that used only branches to mate with visceral and renal vessels. All patients with fenestrations in their device were excluded. Perioperative details, reintervention, occlusion, and death were recorded. Outcome of occlusion or reintervention, as well as a composite outcome of any death, occlusion, or reintervention was planned using a per-patient, and per-branch analysis. Results: In 235 included patients, there were 940 vessels available for placement of mating stent. The average age of included patients was 70 years (SD 7.9), and 179 of the 235 were male. Medical comorbidities included diabetes in 29/234 (12.4%), current smoker in 81/233 (34.8%), and COPD in 77/234 (32.9%). The primary stent deployed was self-expanding in 556 branches, balloon expandable in 231 branches, and was unknown in 92 branches. After a mean of 20.7 months (SD 25) follow-up, there have been 44 incidents of occlusion or reintervention, of which 40 culprit stents are known. Where the stent placed is known, the event rate in renal branches (35/437, 8%) is higher than that of visceral branches (8/443, 1.8%). There is no difference in occlusion or reintervention between self-expanding and balloon expandable stents (HR 0.95, p = .91) but there is a statistically significant difference between renal and visceral artery occlusions (HR 3.51, p = 0.001). Conclusion: There appears to be no difference in occlusion or reintervention rate for branch vessels mated with balloon expandable compared with self-expanding stents. Renal events appear to outnumber visceral events in this population.